Konsep Aksiologi Ilmu dalam Perspektif Barat dan Islam serta Implikasinya terhadap Pendidikan Agama Islam - Putri Firdaus Fahmi; Fitria Faradina Kafa Aula; Siti Fatimah; Pitriatin Pitriatin; Sumiran Sumiran (Jurnal Ilmiah Guru Madrasah, 2025)
The development of contemporary science has generated divergent value orientations between Western and Islamic traditions. Western science emphasizes objectivity, value neutrality, and technical-empirical aspects, whereas the Islamic tradition integrates moral and spiritual values with the pursuit of public benefit (maqāṣid al-sharī‘ah). These differences have significant implications for Islamic Religious Education (IRE), particularly in shaping students’ character, ethics, and spirituality. This study aims to analyze the concept of the axiology of knowledge from Western and Islamic perspectives and to examine its implications for IRE practices. The research employs a qualitative approach through library research, involving a systematic review of primary and secondary literature on Western and Islamic philosophy of science, the axiology of knowledge, and education. Data were analyzed using descriptive-analytical and comparative methods to interpret value orientations, the purposes of knowledge, and their educational implications within both traditions. The findings indicate that Western science initially emphasized value neutrality and objectivity; however, contemporary discourse increasingly highlights the integration of ethics and moral values. In contrast, the Islamic scientific tradition consistently integrates revelation, reason, and empirical experience within a moral, spiritual, and public-benefit-oriented framework. These findings underscore that IRE should be developed holistically by integrating cognitive, ethical, and spiritual dimensions, enabling students to become not only intellectually competent but also morally grounded and socially responsible. The novelty of this article lies in its comparative analysis of Western and Islamic axiological paradigms as a means of strengthening IRE as a platform for character formation and a moral filter in responding to modern science and technology.